2013
DOI: 10.1021/nn3044462
|View full text |Cite
|
Sign up to set email alerts
|

Scalable High-Power Redox Capacitors with Aligned Nanoforests of Crystalline MnO2Nanorods by High Voltage Electrophoretic Deposition

Abstract: It is commonly perceived that reduction-oxidation (redox) capacitors have to sacrifice power density to achieve higher energy density than carbon-based electric double layer capacitors. In this work, we report the synergetic advantages of combining the high crystallinity of hydrothermally synthesized α-MnO2 nanorods with alignment for high performance redox capacitors. Such an approach is enabled by high voltage electrophoretic deposition (HVEPD) technology which can obtain vertically aligned nanoforests with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 77 publications
0
59
1
Order By: Relevance
“…We emphasize that Meng and co-workers [ 46 ] recently reported MnO 2 nanorods-based EC with a power density of 340 kW kg −1 at an energy density of 4.7 Wh kg −1 , and more interestingly, Wang et al [ 47 ] reported 3D graphene/VO 2 nanobelt composite hydrogels as electrodes of supercapacitor that had high-capacitance and high-rate capability with a power density at least 300 kW kg −1 at an energy density of 12 Wh kg −1 . These recordlevel power density is close to, if not higher than the ordinary electrolytic capacitors that are regarded much fast than ECs but with a tiny energy density.…”
Section: +mentioning
confidence: 91%
“…We emphasize that Meng and co-workers [ 46 ] recently reported MnO 2 nanorods-based EC with a power density of 340 kW kg −1 at an energy density of 4.7 Wh kg −1 , and more interestingly, Wang et al [ 47 ] reported 3D graphene/VO 2 nanobelt composite hydrogels as electrodes of supercapacitor that had high-capacitance and high-rate capability with a power density at least 300 kW kg −1 at an energy density of 12 Wh kg −1 . These recordlevel power density is close to, if not higher than the ordinary electrolytic capacitors that are regarded much fast than ECs but with a tiny energy density.…”
Section: +mentioning
confidence: 91%
“…α-MnO 2 nanowires were synthesized hydrothermally using KMnO 4 and MnSO 4 as reactants in aqueous solution14. Specifically, 0.9878, g of KMnO 4 and 0.4226, g of MnSO 4 ·H 2 O were dispersed in 80 ml of deionized (DI) water under constant stir for 30 min to form a purple solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Mn-based oxides are low cost, environmentally friendly and safer with respect to over-charge conditions compared with Co-based oxide electrodes7. Consequently, α-MnO 2 has been extensively studied as a promising cathode material for lithium (sodium and magnesium) ion batteries891011, lithium air batteries1213 and supercapacitors141516.…”
mentioning
confidence: 99%
“…Previous studies mainly play balance between capacitance, conductivity, and flexibility. For examples, hierarchical nanostructures based on carbon cloths and metallic foils were used as the large‐specific‐area substrates for the coating of MnO 2 nanostructures, but the areal capacitances of these electrodes were usually lower than 200 mF cm −2 due to the low loading mass of MnO 2 , and the capacitances of assembled supercapacitors were lower than 50 mF cm −2 , far from the practical application requirements. This problem should be attributed to the low specific area and high density of these scaffolds.…”
Section: Introductionmentioning
confidence: 99%